ON THE DYNAMICS OF PHOTOSYNTHESIS - Osterhout, W. J. V. (The Rockefeller University Press, 1918)
Minute amounts of photosynthesis in marine plants can be accurately measured by adding a little phenolphthalein to the sea water, and observing changes in the color of the indicator. In the case of fresh water aquatics bicarbonates are added. By this method it is found that Ulva which has been kept in the dark begins photosynthesis as soon as it is exposed to sunlight and that the rate steadily increases until a constant speed is attained. This may be explained by assuming that sunlight decomposes a substance whose products either catalyze photosynthesis or enter directly into the reaction. Quantitative theories are developed in order to account for the facts.